Sukses tanpa batas. Panduan perjalanan menuju kesuksesan dunia dan akhirat - SUWAIDAN, Thariq Muhammad (MAGHFIRAH PUSTAKA, 2004)
Sukses tanpa batas. Panduan perjalanan menuju kesuksesan dunia dan akhirat